Democracy and child mortality: Evidence from Sub-Saharan Africa - Sharma, Anand; Sharma, Vipin; Tokas, Shekhar (Asian Development Policy Review, 2024)
Many countries in Sub-Saharan Africa (SSA) are characterized by low levels of democracy and show dismal health outcomes. This paper examines the association between democracy and child mortality rates in the 40 Sub-Saharan African (SSA) countries using data from 2000 to 2019. Democracy is measured using three indices prepared by Polity5, Varieties of Democracy (V-Dem) Institute and Freedom House. The data on infant mortality and neonatal mortality rates are taken from the World Development Indicators of the World Bank. The panel data regression results indicate that democracy is negatively linked to infant and neonatal mortality rates. This finding implies that a greater degree of democracy in SSA countries is associated with lower child mortality rates. The results of this study are robust for alternative measures of democracy. The paper also finds that education, urbanization, immunization, economic freedom, and water facilities are negatively associated with child mortality rates. These findings suggest that SSA countries should formulate policies that promote a robust democracy and strengthen the political rights of their citizens. These countries should invest in education, infrastructure, and immunization and implement policies that raise the pace of urbanization and improve economic freedom. These policy measures are likely to favorably affect child mortality rates in the SSA countries.